2019
DOI: 10.1002/jmri.26892
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatic imaging using MRI

Abstract: FIGURE 6: Dynamic curves of relative signals after injection of 17O-labeled water. Dynamic curves of relative signal intensity. A bolus injection of saline or 17O was initiated 120 seconds after starting a scan. Significant drops in signal were observed in the cerebral cortex (a), choroid plexus (d), ventricle (e), and subarachnoid space (f) in the 17O condition, while only slight reductions in signal were noted in the basal ganglia/thalamus (b) and white matter (c). In the cerebral cortex, choroid plexus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
162
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(166 citation statements)
references
References 65 publications
3
162
1
Order By: Relevance
“…The GBCA leaks from the impaired portion of the BBB, the peripheral part of the cranial nerves, choroid plexus, circumventricular organs, and subarachnoid vessels. [2][3][4][5]14,20,25,27 It has been reported that the CSF signal intensity in the lateral ventricles and the prepontine cistern was decreased at 24 h compared to 3 h post-administration of GBCA. 1 Decreased enhancement in the CSF at 24 h is consistent with the results of the present study.…”
Section: Csf Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…The GBCA leaks from the impaired portion of the BBB, the peripheral part of the cranial nerves, choroid plexus, circumventricular organs, and subarachnoid vessels. [2][3][4][5]14,20,25,27 It has been reported that the CSF signal intensity in the lateral ventricles and the prepontine cistern was decreased at 24 h compared to 3 h post-administration of GBCA. 1 Decreased enhancement in the CSF at 24 h is consistent with the results of the present study.…”
Section: Csf Enhancementmentioning
confidence: 99%
“…2,3,21,22 The glymphatic system is the waste clearance system of the brain and has attracted much attention from a wide range of investigators. [23][24][25] Establishment of a method for the evaluation of the glymphatic system is a hot research topic in the neuroscience field. 26 Currently, the distribution patterns of intravenously administered GBCA in various fluid spaces of humans are under intense investigation as the first step of the glymphatic system and as a measure of BBB integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have underlined the potential of Diffusion MRI to investigate the glymphatic system [7,22–24] and the ADC has been proposed as a biomarker of AQP gene expression, as earlier studies have demonstrated that the ADC obtained with high b values was correlated with the amount of increasing expression of AQP1 in glioblastoma cell lines [37]. In this study, we have investigated whether two diffusion MRI markers, Sindex and sADC, could detect changes in astrocyte activity induced by a pharmacological challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This clearance system has been evidenced initially using fluorescent tracers and 2-photon microscopy in rodents [1], however MRI offers a more versatile approach. MRI studies have relied on the intrathecal or intravenous injections of gadolinium-based contrast agents (GBCAs) as tracers [7,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation